设 [img=66x25]1803cd94b2014ef.png[/img]由参数方程[img=169x26]1803cd94ba855bf.png[/img]确定,则[img=27x46]1803cd94c3447e3.png[/img]等于( ).
未知类型:{'options': ['', '', '', ''], 'type': 102}
未知类型:{'options': ['', '', '', ''], 'type': 102}
举一反三
- 设 [img=66x25]1803cd94b2014ef.png[/img]由参数方程[img=169x26]1803cd94ba855bf.png[/img]确定,则[img=27x46]1803cd94c3447e3.png[/img]等于( ). A: [img=106x53]1803cd94ccfc109.png[/img] B: [img=106x53]1803cd94d66173a.png[/img] C: [img=106x53]1803cd94e1baca0.png[/img] D: [img=106x53]1803cd94ee22b14.png[/img]
- 设函数y=f(x)由参数方程[img=164x19]17da62a295a4708.jpg[/img]所确定,则[img=19x34]17da4275482315f.jpg[/img]为 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 设函数[img=66x25]1803457cf4c172e.png[/img]由参数方程[img=153x61]1803457cfe77e36.png[/img]所确定,则[img=46x46]1803457d06fa8cb.png[/img]( ). 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 2、由方程[img=182x28]1802e444a9d8219.png[/img]确定函数y=f(x)的二阶导数[img=27x46]1802e444b2473e0.png[/img]为( ) 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 2、由方程[img=182x28]1802e44234cea13.png[/img]确定函数y=f(x)的二阶导数[img=27x46]1802e4423cf0f43.png[/img]为( ) 未知类型:{'options': ['', '', '', ''], 'type': 102}